APAKAH INI INTERNET INFIDELITY? PERSEPSI DARI ORANG BERPACARAN VERSUS MENIKAH - Yulian Hermanus Wenno; Criezta Corlefura; cynthia Petra Haumahu (Program Studi Bimbingan dan Konseling, Universitas Pattimura, 2021)
This study aims to investigate empirically the difference in the perception of internet infidelity between married people and those who are still dating. There were 62 respondents who had filled out the research questionnaire, but only 58 of them were eligible to be processed. Hypothesis testing using the Manova test. Based on the results of quantitative data processing using SPSS, it can be seen that this study failed to confirm the difference in the perception of internet infidelity between married people and those who were still dating. Keywords: Internet Infidelity, Intimate Action, Non-Intimate Action, Marital Status.